Low-Temperature Fabrication of Stable Black-Phase CsPbI3 Perovskite Flexible Photodetectors Toward Wearable Health Monitoring - Zhao, Yingjie; Sun, Yicheng; Pei, Chaoxin; Yin, Xing; Li, Xinyi; Hao, Yi; Zhang, Mengru; Yuan, Meng; Zhou, Jinglin; Chen, Yu; Song, Yanlin (Nano-Micro Letters, 2024)
Flexible wearable optoelectronic devices fabricated from organic–inorganic hybrid perovskites significantly accelerate the development of portable energy, biomedicine, and sensing fields, but their poor thermal stability hinders further applications. Conversely, all-inorganic perovskites possess excellent thermal stability, but black-phase all-inorganic perovskite film usually requires high-temperature annealing steps, which increases energy consumption and is not conducive to the fabrication of flexible wearable devices. In this work, an unprecedented low-temperature fabrication of stable black-phase CsPbI3 perovskite films is demonstrated by the in situ hydrolysis reaction of diphenylphosphinic chloride additive. The released diphenyl phosphate and chloride ions during the hydrolysis reaction significantly lower the phase transition temperature and effectively passivate the defects in the perovskite films, yielding high-performance photodetectors with a responsivity of 42.1 A W−1 and a detectivity of 1.3 × 1014 Jones. Furthermore, high-fidelity image and photoplethysmography sensors are demonstrated based on the fabricated flexible wearable photodetectors. This work provides a new perspective for the low-temperature fabrication of large-area all-inorganic perovskite flexible optoelectronic devices. Highlights: 1 Low-temperature fabrication of black-phase CsPbI3 perovskite films is first demonstrated by using diphenylphosphinic chloride additive under 30–50 °C, arising from the steric effect and chloride insertion engineering. 2 Large-area high-quality all-inorganic perovskite films with fewer defects enhanced crystallographic orientation, and excellent environmental stability is fabricated. 3 The record performances are demonstrated for flexible wearable photodetectors with a responsivity of 42.1 A W−1, a detectivity of 1.3 × 1014 Jones, high-fidelity image, photoplethysmography sensor functions, and high mechanical stability.